Absorbed dose and image quality of Varian TrueBeam CBCT compared with OBI CBCT. Issue 12 (December 2016) - Kawahara, Daisuke; Ozawa, Shuichi; Nakashima, Takeo; Suzuki, Tatsuhiko; Tsuneda, Masato; Tanaka, Sodai; Ohno, Yoshimi; Murakami, Yuji; Nagata, Yasushi
Graphical abstract: Highlights: The efficiency of Varian TrueBeam CBCT systems is evaluated through comparison with that of OBI CBCT. Image quality of AAPM TG-142 using TB CBCT is equal to or greater than that of OBI CBCT. Uniformity for a larger body size with TB CBCT is greater than that with OBI CBCT. Radial dose profile and patient organ dose with TB CBCT smaller than OBI CBCT. Abstract: Purpose: Nowadays, patient positioning and target localization can be verified by using kilovolt cone beam computed tomography (kV-CBCT). There have been various studies on the absorbed doses and image qualities of different kV-CBCT systems. However, the Varian TrueBeam CBCT (TB CBCT) system has not been investigated so far. We assess the image quality and absorbed dose of TB CBCT through comparison with those of on-board imager (OBI) CBCT. Methods: The image quality was evaluated using two phantoms. A CATPHAN phantom measured the image quality parameters of the American Association of Physicists in Medicine Task Group 142 (AAPM TG-142) report. These factors are the pixel value stability and accuracy, noise, high-contrast resolution, low-contrast resolution, and image uniformity. A H2 SO4 phantom was used to evaluate the image uniformity over a larger region than the CATPHAN phantom. In evaluating the absorbed dose, the radial dose profile and the patient organ doses at the prostate and rectum levels were evaluated. Results: The image quality parameters of AAPM TG-142 using TB CBCT are equal to or greater than those of OBI CBCT. In particular, the contrast-to-noise ratio with TB CBCT is 2.5 times higher than that with OBI CBCT. For the test of a large field uniformity, the maximum difference in the Hounsfield unit (HU) values between the centre and peripheral regions is within 30 HU with TB CBCT and 283 HU with OBI CBCT. The maximum absorbed dose with TB CBCT is decreased by 60%. Conclusions: We find that the image quality improved and the absorbed dose decreased with TB CBCT in comparison to those with OBI CBCT. Its image uniformity is also superior over a larger scanning range.